Effects of PMSG and HCG on estradiol and progesterone levels from common palm civets (Paradoxurus hermaphroditus) - Hien, Nguyen Thi Thu; Phuong Thao, Nguyen Thi; Ngoc Tram, Vo Le; Thanh Binh, Nguyen (Vietnam Journal of Biotechnology, 2021)
The common palm civets (Paradoxurus hermaphroditus) belong to the civets family (Viverridae), the carnivores order (Carnivora). This animal is widely distributed in South and Southeast Asia. Currently, the civets are raised quite popular in Vietnam. The delay in breeding for the first time and slow in the rut has reduced economic efficiency in civet farming. This study was carried out to evaluate the effectiveness of different doses of hormones (PMSG, HCG) on sex hormonal changes in the civets. A total of 54 female civets were used in this experiment. PMSG/HCG intramuscularly in 3 formulations (CT): CT1: 20 IU PMSG + 10 IU HCG; CT2: 30 IU PMSG + 15 IU HCG; CT3: 40 IU PMSG + 20 IU HCG. The results showed that E2 level in the feces of the civets in the treatments began to increase at the first day after injection and peaked on the second day. P4 concentration in the experimental civet groups began to increase in the first day and peaked on the 3rd or 4th day. The amounts of E2 and P4 in the feces of the civet group injected with CT3 was significantly higher than that of CT1 and CT2 groups (P <0.05). This result provides reliable references for subsequent studies on the use of gonadotropin on the common palm civets to both exploit and preserve the ex-situ conservation of this rare wildlife.